1988
DOI: 10.1002/ajmg.1320290122
|View full text |Cite
|
Sign up to set email alerts
|

Paracentric inversion of Xq and ovarian dysfunction

Abstract: We report on a paracentric inversion X(q13 q24) in a 20-year-old woman with ovarian dysfunction. The findings add evidence on the role of breakpoints in Xq13 and Xq24 in causing ovarian dysfunction. A review of the published data on paracentric inversion of chromosome X is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nemeth et alreported an infertile man with a Klinefelter like phenotype having an X inversion with 46,Y,inv(X) (q12q25) 28 . Dar et alreported that a woman had dysgenesis with primary amenorrhea and she had a de novo inv (X) (q13 q24) 29 . Pericentric inversion of chromosome 1, 3, 5, 6 and 10 are related to abnormal sperm production in infertile men.…”
Section: )mentioning
confidence: 99%
“…Nemeth et alreported an infertile man with a Klinefelter like phenotype having an X inversion with 46,Y,inv(X) (q12q25) 28 . Dar et alreported that a woman had dysgenesis with primary amenorrhea and she had a de novo inv (X) (q13 q24) 29 . Pericentric inversion of chromosome 1, 3, 5, 6 and 10 are related to abnormal sperm production in infertile men.…”
Section: )mentioning
confidence: 99%
“…19,20) One article reported that a woman with de novo inv(X)(q13q24) had ovarian dysgenesis such as primary amenorrhea and absence of pubertal development. 21) Most paracentric inversions are considered to be harmless. However, meiotic crossover in the inverted segment may generate chromosomally unbalanced gametes.…”
Section: )mentioning
confidence: 99%